Investigations of Social Infrastructure in Rural Settlements of Borsod County - Sikos, T. Tamás (Discussion Papers, 1987)
Since World War 2, the national economy of Hungary has undergone a significant socio-economic transformation resulting from the building of socialism. In the recent phase of development, the main task of society and social policy has been to reveal the disproportions in the development of individual regions and to highlight the variations in the living standards between the urban and rural populations. Current regional policy pays special attention to the development of infrastructure and settlement network. The inadequate development of social infrastructure and communication networks in rural settlements leads to undesirable phenomena such as outmigration, distortion of the demographic structure of rural settlements, shortage in the supply of agricultural labour and the emergence of depressed regions. All these facts inspired the author to examine the social infrastructure in rural settlements. The basic aim of the research was to investigate the difference among regional levels of social infrastructure in rural settlements of Borsod-Abaúj-Zemplén county (North-Hungary). A great number of studies by Hungarian researchers have been published investigating primarily public administration and economic problems, and the stratification and migration of population in rural settlements. In these studies attention has been given to the differentiation in regional development levels and the typology of rural settlements of Hungary, but a complex economic and economic-geographical research into the typology of social infrastructure of rural settlements has not yet been carried out. The statistical data base for 1980 and data collected by the Council of Borsod-Abaúj-Zemplén county contributed largely to the present investigation. In the framework of the present research, with the help of mathematical and statistical tools, the author was able to determine the scope of elements as well as that of the extent to which they shape the development of social infrastructure of rural settlements and to elaborate the typology of social infrastructure of rural settlements.